Relationship between Individu Characteristics and Environmental Condution of Houses with Pneumonia in Children Under Five at Tarus Health Center - Taopan, Sumardiana; Purnawan, Sigit; Riwu, Yuliana Radja (Timorese Journal of Public Health, 2024)
Tarus Health Center, have 358 cases of pneumonia in children under the age of five in 2018, 377 cases in 2019, and 138 fewer cases in 2020. The goal of this study was to examine the variables that affect the prevalence of pneumonia in children at the Tarus Health Center between the ages of 12-59 months. Analytical observation with a case control design is the methodology employed. Simple random sampling is the sampling method employed. 34 respondents made up the case sample and 34 respondents made up the control sample in this study. Chi-square test was used to evaluate the data. The findings indicated that there was no significant relationship between the type of floor (p-value 0.474 with OR 2.214) and the incidence of pneumonia in children under five, but there was a significant relationship between nutritional status (p-value 0.013 with OR 5.250), low birth weight (p-value 0.027 with OR 3.519), exclusive breastfeeding (p-value 0.025 with OR 3.656), and wall type (p-value 0.007 with OR 4.643). Prevention of pneumonia can be done by improving the nutritional status of children, giving exclusive breastfeeding and using types of walls that meet health requirements, namely made of walls.